Case Report: Pulmonary mucormycosis caused by Rhizopus microsporus in a patient with chronic obstructive pulmonary disease - Wang, Shanshan; Liu, Yanqing; Hu, Liqing; Qian, Guoqing; Mo, Yijun (Frontiers in Medicine, 2025)
BackgroundWe report a rare case of pulmonary mucormycosis caused by Rhizopus microsporus, which is rare in patients with chronic obstructive pulmonary disease. Rhizopus microsporus had been reported as the most common etiological agent associated with human infections, except Rhizopus oryzae in some studies.Case presentationWe described a case of 81-year-old man with pulmonary mucormycosis caused by Rhizopus microsporus but no other apparent risk factors including diabetes. The diagnosis mainly relied on sputum cultures and clinical manifestations. Despite antifungal therapy, his condition worsened, resulting in mortality.ConclusionIn this case, the patient had no underlying diseases such as diabetes or solid tumors. Clinicians should be aware of routine pathogenic microbiological tests of pulmonary mucormycosis in patients with chronic obstructive pulmonary disease. Early and aggressive treatment can lead to improved prognosis.